Keragaman Jenis Pohon Pelindung Jalan Pada Jalur Hijau Kota Pekanbaru - Fauziah, Yuslim; Zam, Syukria Ihsan (Jurnal Pilar Sains, 2005)
The research on diversity of protecting plant at Pekanbaru city had carried out on six main roads. Thestudy had been done with survey methods by transect. One main road is a transect that divide into someintervals 100 meter each ones. Data collecting are diameters of breath high and cover of a tree is length oftransect that intercepts by cover of each ones. Parameters are Density, Relative Density, Frequency,Relative Frequency, Dominancy, Relative Dominancy, Coverage, Importance Value and Diversity Index.Another data that collecting are air temperature, relative humidity, light intensity, particulate contents inleaf surface. The results in this research that protecting plants at Pekanbaru city include 13 species eith 8family, that dominance with Pterocarpus indicus, Swietenia mahagoni and Acacia mangium. Diversityindex each location 0.692-1.641, density 1.583-6.6 trees/100 meter length of roads and coverage of trees7.285-30.341 meters/100 meters length of roads. Particulate contens are 0.219-0.580 mg/cm2 of leafsurface.